The relationship between the incidence of winners/errors and the time spent in different areas of the court in elite tennis - Martinez-Gallego, R.; Guzmán, J. F.; James, N.; Ramón-Llin, J.; Crespo, M.; Vuckovic, G. (Journal of Human Sport & Exercise, 2013)
Winners and errors have been two of the most studied performance indicators in tennis, contributing to the prediction of match outcome and definition of the playing style of the players. Furthermore, the position occupied by the player on the court has also been shown to be a good indicator of both the final result and style of play. The aim of this study was to examine whether there were differences between game winners and losers in terms of number of winners and errors, and if there were differences in them according to the player's position. 8 matches of the 2011 ATP tournament 500 Valencia were recorded and analysed using SAGIT, a computer vision tracking system that allowed both players` movements to be tracked automatically. The software was programmed to divide each half of the court into offensive and defensive zones. The data were divided in games (N = 188) for analysis purposes and the outcomes of the rallies were classified as winners, forced and unforced errors. The proportionate frequency of unforced errors for losers was higher than winners, and the proportionate frequency of winners and opponent`s forced errors was higher for winners than for losers. The time spent of winners in the offensive zone correlated with the percentage of winners and opponent`s forced errors, while for the losers time spent in the offensive zone correlated with the percentage of unforced errors. These results suggest that when game winners are in offensive zone they take advantage to hit more winners or force opponent`s error. On the contrary when game losers are in offensive zone, they commit more unforced errors. Future investigations should consider shots played in each zone separately.